The Future of Taxation in the Digital Era : Challenges and Strategies of Indonesia's Tax Policy - Saman Saman (Harmoni Economics: International Journal of Economics and Accounting, 2025)
Digital transformation has fundamentally changed the structure of the global economy, creating a new paradigm in the tax system that demands a thorough adaptation. This systematic literature review research aims to explore the future of digital taxation in Indonesia through a comprehensive analysis of tax policy challenges and strategies. The research methodology adopts the PRISMA protocol with a systematic search of international and national databases, conducting a strict selection from 309 articles to filter 10 quality journals for in-depth review. The research uses a qualitative meta-synthesis approach to analyze themes, compare policy strategies, and integrate findings across studies. The results of the study reveal that Indonesia's digital economy will reach USD 82 billion in 2023, with a projected USD 146 million in 2025, supported by internet penetration of 221,563,479 users. Key findings show a significant increase in the e-filing system from 68.2% in 2016 to 83.4% in 2022, as well as a positive perception of 70% of Generation Z towards digital tax education. The research identified key challenges including the digital divide, low technology literacy, and regulatory complexity. The conclusion emphasizes the need for a holistic approach that integrates technology, education, and social participation through digital infrastructure investments, inclusive literacy programs, adaptive regulatory frameworks, and multi-stakeholder collaboration to realize a fair, efficient, and inclusive digital tax ecosystem.